1359 Everyone Deserves to Smile: An Audit on The Success Rate of Dental Implants in Complex Maxillofacial Patients. (12th October 2021) - Lugaric, P; Frezzini, C; Patterson, A
Abstract: Aim: To determine the success rates of dental implants in complex patients treated in the Oral and Maxillofacial Surgery Department at Rotherham General Hospital (RGH). Method: All patients who received dental implants in the period January 2010 – March 2017 at RGH were included in the audit. Retrospective. Using Consultant personal database and clinical records. Failure defined clinically as the loss of the implant. Standards: 90% local standard Results: 68 dental implants were placed in 22 patients: 15 patients head and neck reconstruction, 5 atrophic edentulous patients, 2 trauma. 14 M, 8 F Age 25 – 84 6 implants failed (3 patients) Survival rate 91.2% Conclusions: Survival rates for dental implants in the literature is variable ranging from 91 -96% in native bone and mucosa and 46 - 98% in irradiated tissue. In Rotherham General Hospital implants are placed largely in patients with significant adverse factors such as treatment for oral cancer. The survival rate achieved was in excess of the local standards set in a compromised group of patients. This audit highlights the importance of dental rehabilitation in complex maxillofacial patients and details some of the difficulties that can be encountered and their solutions.